The importance of introducing medical legislation in the university training program for students - George Nicola; Irina Maria Gheorghiu; Sanziana Scarlatescu; Paula Perlea (Amaltea Medical Publishing House, 2021)
The place of medical legislation in the university curriculum remains somehow uncertain and should be identified more clearly. A more robust knowledge base on the law is needed to enable medical students to develop sufficient legal competence to manage the challenges of future practice. Further research is needed to identify the most effective methods of teaching, learning and assessing legal knowledge and skills, during and after the completion of initial medical education. An in-depth analysis of resources shows that there is no robust evidence base that evaluates the impact in different curricular structures of the efficient methods in developing the knowledge, skills, attitudes, and behaviors needed in medical practice of student. Moreover, only a limited number of studies refer to the results and effectiveness of teaching and learning the elements of medical legislation.